Publicidade das big techs sob o olhar crítico da Economia Política da Desinformação - Alencar, Marta Thaís (2023)
It is in the electoral process that fake news gains greater visibility, and its proliferation is commonly associated with closed groups, with deeply held and slightly contradictory beliefs, consolidating the polarization in digital social networks. In this regard, convictions – moral, party-political and socio-cultural – influence a selection of content to consume and share on networks. This scenario is worrisome and has served as a basis for research on the impact of disinformation on elections in Brazil. In recent years, studies have been produced and disseminated, but disinformation has gained greater notoriety in the country since the 2018 elections (DOURADO, 2021; MELLO, 2020). Starting from a selective and analytical reading, this article aims to approach the proposed theme under the critical eye of researchers in the Political Economy of Communication (BOLAÑO, 2000; MARTINS, 2020; VALENTE, 2020), building its corpus from the unfolding of the Fake News Bill (current version of PL 2630/2020) and based on the performance of big techs in the advertising market.